HOLINESS IN THE EASTERN CHRISTIAN TRADITION (ON THE EXAMPLE OF SAINTS FROM THE KYIV-PECHERSK LAVRA) (Религиски дијалог и соработка, 2022)
The article found out that holiness in the Eastern Christian traditionis spiritualperfection. Moreover, in the understanding of human holiness there is a constantandsincere spiritual improvement, which takes the individual to a higher level of spirituality.In addition, it was analyzed that spirituality is interpreted in terms of activity, inparticular,the path to spiritual height is achieved by a lot of work on oneself, namely: therejectionof everything created, material - everything that can distract fromthe achievementofthe desired. The etymology of the concept of holiness and the search for analoguesinpre-Christian ones are also consideredlinguistic and religioustraditions The priorityinthe study is the image of holiness, as a peculiar summary of the formation of themoralideal of Ancient Russia. This statement is demonstrated on the personages intheKyiv-Pechersk Pateryk, in particular, on Saints Anthony the Great and Theodosius of Pechersk.Their thorny elevation is emphasized, which is full of humility, reverence, patienceandwork in the name of Jesus Christ. Attention is drawn to the visual connectionbetweenthe holy and the earthly, the provision of certain aesthetic images (glow, brilliance, sunrays, golden color), which speaks of the vision and influence of the emotional onthesacred. It is emphasized that holiness is a powerful factor influencing humanfeelings.Itis updated that the phenomenon of holiness gives rise to a blessed feeling of its equal,but still dependent on it, which does not oppress, and elevates to the heights of theWorldObjective Spirit. Due to the feeling of its involvement in the Universe, the spiritual andmoral state of a person acquires a spiritual motive. In this environment, a personlosesa sense of completeness and receives a guarantee of a bright continuation of lifeafterdeath. A person is not afraid, he believes in his arrival in God, if he cleanses himselfofeverything “sly” and reaches the highest point of bliss.